2015
DOI: 10.1152/ajplung.00099.2015
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ-induced JAK/STAT, but not NF-κB, signaling pathway is insensitive to glucocorticoid in airway epithelial cells

Abstract: Although the majority of patients with asthma are well controlled by inhaled glucocorticoids (GCs), patients with severe asthma are poorly responsive to GCs. This latter group is responsible for a disproportionate share of health care costs associated with asthma. Recent studies in immune cells have incriminated interferon-γ (IFN-γ) as a possible trigger of GC insensitivity in severe asthma; however, little is known about the role of IFN-γ in modulating GC effects in other clinically relevant nonimmune cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Based on ChIP data, once established, this pathway may actually be perpetuated by chronic steroid therapy through interactions between GR and STAT1 on target sites in the CXCL10 promoter. As observed in our study using monocytic cells, in a previous study of air-way epithelial cells derived from patients with chronic obstructive pulmonary disease, CS did not inhibit IFN-γ-induced STAT1 phosphorylation (57). This inability of CS to inhibit STAT1 phosphorylation can be expected to facilitate GR-STAT1 collaboration, as observed in our ChIP assay.…”
Section: Discussionsupporting
confidence: 82%
“…Based on ChIP data, once established, this pathway may actually be perpetuated by chronic steroid therapy through interactions between GR and STAT1 on target sites in the CXCL10 promoter. As observed in our study using monocytic cells, in a previous study of air-way epithelial cells derived from patients with chronic obstructive pulmonary disease, CS did not inhibit IFN-γ-induced STAT1 phosphorylation (57). This inability of CS to inhibit STAT1 phosphorylation can be expected to facilitate GR-STAT1 collaboration, as observed in our ChIP assay.…”
Section: Discussionsupporting
confidence: 82%
“…Likewise data from DUSP1 knock-out mouse models directly support these findings, and taken together this emphasizes the in vivo relevance of the current findings (12,46). Additionally, IRF1 is activated by interferons (IFNs) via the STAT1 transcription factor, and IFN-and STAT1-mediated inflammatory responses are also insensitive to glucocorticoids (12,65). However, because the deficiency of DUSP1 attenuates IFN␥-and IRF1-dependent IL12 expression, a wider relevance to these data is anticipated (12,66).…”
Section: Negative Regulation Of Irf1 By Mapkssupporting
confidence: 61%
“…It seems thus that the medications did not significantly affect our results. Likewise, a recent study on asthma patients showed insensitivity of IFN-γ-induced JAK/STAT signaling pathways to corticosteroid effects in epithelial cells [34].…”
Section: Discussionmentioning
confidence: 98%